Ascorbic acid enhanced ferrous/persulfate system for degradation of tetracycline contaminated groundwater. Issue 50 (9th November 2022) - Wang, Hengyi; Zhao, Liyang; Li, Qian; Liu, Xixiang; Liang, Liying; Cen, Jianmei; Liu, Yan; Pan, Honghui
Abstract : Persulfate (PS) activated by Fe(ii ) has been widely investigated for degradation of contaminants. Abstract : Persulfate (PS) activated by Fe(ii ) has been widely investigated for degradation of contaminants. However, the Fe(ii )/PS systems used for actual contaminated groundwater remediation have been restricted by circulation of Fe(iii )/Fe(ii ). Herein, an ascorbic acid (AA) enhanced Fe(ii )/PS system was developed for degradation of tetracycline (TC) contaminated groundwater. The influence of Fe(ii ), AA, PS dosage and pH on degradation of TC was investigated, the free radicals produced in the reaction were identified and the reusability of Fe(ii ) in the Fe(ii )/PS/AA system for degradation of TC was also evaluated. The results showed that AA significantly promoted the degradation of TC in the Fe(ii )/PS system, and a degradation rate of 86% for TC was achieved at 60 min. The dominant oxidant species for contaminant degradation in the Fe(ii )/PS/AA system is ˙OH. Appropriate Fe(ii ), AA and PS dosage can improve the degradation rate of TC. Moreover, the degradation rate of TC in the Fe(ii )/PS/AA system under acidic conditions is higher than that under alkaline conditions. With the increase of reaction time, TC can also be completely degraded even with a little Fe(ii ) or under alkaline conditions in the Fe(ii )/PS/AA system, and Fe(ii ) showed a good reusability for the degradation of TC. Thus, the AA-enhanced Fe(ii )/PS system for the degradation of contaminants displays the advantages of less Fe(ii ) consumption and a wide range of pH. This method provides a new strategy for in situ remediation of contaminated groundwater.